Recordações e práticas de uma jornada universitária - Arruda, Antonia da Conceição Almeida (Brasil, 2024)
In this final course paper, I present a description of the facts and activities I consider most important in my life's journey, from my childhood to my first contact with school in elementary education, high school, and higher education. I will also include accounts of pedagogical practices that Werle essential in my training as a future educator. In the first chapter, I will provide a brief narrative about the moments that marked my life's trajectory from childhood to entering higher education. In the second chapter, I will present the ideas of some authors that underpin the entire narrative discussed during the internships of the pedagogy course at the Federal University of Amazonas. These experiences not only contributed to my professional training but also helped me understand what it means to be an educator who cares about forming critically reflective human beings, capable of continuously adapting their methodologies to meet individual needs. The contact with teaching practices during the supervised internships in early childhood education, the early years of elementary school, and school management, supported by the theoretical knowledge gained from studied disciplines, theorists, and practices developed during the degree, provided me with rewarding experiences that I will carry beyond my professional life. Finally, but no less importantly, I outline some perspectives I intend to achieve after completing the pedagogy course to further enhance my professional development as an educator.